2020
DOI: 10.15415/jnp.2020.72024
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations Induced by Temperature Changes in Rotavirus VP6 Protein Immersed in an Electric Field and Their Effects on Epitopes of The Region 300-396

Abstract: Rotavirus diarrhea is an infectious intestinal disease that causes about 215 thousand deaths annually in infants under five years old. This virus is formed by three layers of concentric proteins that envelop its genome, from which VP6 structural protein is the most conserved among rotavirus serotypes and an excellent vaccine candidate. Recent studies have shown that structural proteins are susceptible to losing their biological function when their conformation is modified by moderate temperature increments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Theoretical reports have suggested that electric field intensities of at least 0.10 Vnm -1 can cause subtle movements of atoms within proteins and promote conformational changes [16]. Moreover, in previous work, we used 1.0 Vnm -1 to induce structural variations in other viral proteins [17]. Based on the previous statements, we initially disturbed RBD with stimulus 1, and after that, we used a second stimulus E 0 = 2.9 Vnm -1 with twice the intensity: ω = 300 ps -1 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical reports have suggested that electric field intensities of at least 0.10 Vnm -1 can cause subtle movements of atoms within proteins and promote conformational changes [16]. Moreover, in previous work, we used 1.0 Vnm -1 to induce structural variations in other viral proteins [17]. Based on the previous statements, we initially disturbed RBD with stimulus 1, and after that, we used a second stimulus E 0 = 2.9 Vnm -1 with twice the intensity: ω = 300 ps -1 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%